Creative Collaboration - Yong, Titus (Encyclopedia of Creativity, Invention, Innovation and Entrepreneurship, 2020)
Creative collaboration happens when a creative process is undertaken by two or more individuals, teams, entities, or organizations for a project or challenge of common concern. Typically, the project is too challenging to be undertaken alone; and if done satisfactorily, the outcome is would be both novel and useful. Members can collaborate either physically or remotely through electronic (online creative collaboration) or other means at all or different phases of the project.
Keywords: Co-création; Innovation; Participation; Réservé UdeM